Continuous Glucose Monitoring and Time in Range: Association with Adverse Outcomes among People with Type 2 or Gestational Diabetes Mellitus - Bitar, Ghamar; Cornthwaite, Joycelyn A.; Sadek, Sandra; Ghorayeb, Tala; Daye, Nahla; Nazeer, Sarah; Ghafir, Danna; Cornthwaite, John; Chauhan, Suneet P.; Sibai, Baha M.; Fishel Bartal, Michal (American Journal of Perinatology, 2023)
Objective Continuous glucose monitoring (CGM) has become available for women with type 2 diabetes mellitus (T2DM) or gestational diabetes mellitus (GDM) during pregnancy. The recommended time in range (TIR, blood glucose 70–140 mg/dL) and its correlation with adverse pregnancy outcomes in this group is unknown. Our aim was to compare maternal and neonatal outcomes in pregnant people with T2DM or GDM with average CGM TIR values >70 versus ≤70%.Study Design We conducted a retrospective cohort study of all individuals using CGM during pregnancy from January 2017 to June 2022. Individuals with type 1 diabetes mellitus, or those missing CGM or delivery data were excluded. Primary composite neonatal outcome included any of the following: large for gestational age, NICU admission, need for intravenous glucose, respiratory support, or neonatal death. Secondary outcomes included other maternal and neonatal outcomes. Regression models were used to estimate adjusted odds ratio (aOR) and 95% confidence interval (CI).Results During the study period, 141 individuals with diabetes utilized CGM during pregnancy, with 65 (46%) meeting inclusion criteria. Of the study population, 28 (43%) had TIR ≤70% and 37 (57%) had TIR > 70%. Compared with those with TIR > 70%, the primary composite outcome occurred more frequently in neonates of individuals TIR ≤70% (71.4 vs. 37.8%, aOR: 4.8, 95% CI: 1.6, 15.7). Furthermore, individuals with TIR ≤70% were more likely to have hypertensive disorders (42.9 vs. 16.2%, OR: 3.9, 95% CI: 1.3, 13.0), preterm delivery (54 vs. 27%, OR: 3.1, 95% CI: 1.1, 9.1), and cesarean delivery (96.4 vs. 51.4%, OR: 4.6, 95% CI: 2.2, 15.1) compared with those with TIR >70%.Conclusion Among people with T2DM or GDM who utilized CGM during pregnancy, 4 out 10 individuals had TIR ≤70% and, compared with those with TIR > 70%, they had a higher likelihood of adverse neonatal and maternal outcomes.Key Points
Keywords: diabetes; pregnancy; continuous glucose monitoring; time in range; neonatal outcomes; maternal outcomes